The Influence of Al2O3 Nanoparticles on Electron Transport in a Polymer Solar Cell - Mussabekova, A.K.; Aimukhanov, A.K.; Zeinidenov, A.K.; Ziyat, A.Z.; Abdrakhman, K.T.; Аlexeev, A.M. (Bulletin of the Karaganda University. “Physics” Series., 2025)
The effect of Al2O3 nanoparticles on the electron transport of SnO2-based electron transport layer (ETL) in polymer solar cells was studied. Comprehensive studies of the morphology, optical, electrophysical and photoelectric properties of the composite films were carried out. It was found that doping SnO2 films with Al2O3 nanoparticles leads to a decrease in the surface roughness of the composite films. According to the absorption spectra, it was shown that an increase in the concentration of Al2O3 nanoparticles in SnO2 films leads to a decrease in the optical bandgap. Analysis of the impedance spectra showed that there is a critical concentration of Al2O3 nanoparticles at which the maximum improvement in the electrotransport characteristics of SnO2 films is observed. At high Al2O3 concentrations (over 15 %), a decrease in electron mobility and an increase in recombination in the studied composite film are observed. Photovoltaic measurements have demonstrated that the highest efficiency of 2.8 % polymer solar cells is achieved at an optimal concentration of Al2O3 nanoparticles equal to 15 %. Further increase in the content of Al2O3 nanoparticles leads to a decrease in the efficiency of polymer solar cells. Since localized negative charges in Al2O3 nanoparticles create a local electric field, they screen the recombination of minority charge carriers in ETL SnO2. This suppresses the leakage current in devices. Therefore, it is important to investigate the charge transfer mechanism in SnO2:Al2O3 films and evaluate their potential for application in polymer solar cells.
Al2O3 нанобөлшектерінің полимерлі күн элементіндегі электрондарды тасымалдауға əсері
Влияние наночастиц Al2O3 на электронный транспорт в полимерном солнечном элементе
Keywords: SnO2; Al2O3; morphology; absorption; band gap; Bode plots; impedance; current-voltage characteristics